PENGEMBANGAN MEDIA INTERAKTIF BERBASIS PENDEKATAN SCIENCE, TECHNOLOGY, RELIGION, ENGINEERING, ART AND MATHEMATICS PADA MATERI IKATAN KIMIA - Dewi, Sari Tirta; Yenti, Elvi; Refelita, Fitri; Kurniawati, Yenni (Journal of Chemistry Education and Integration, 2025)
This research was motivated by the lack of learning media using information and communication technology and the creation of student-centred, interactive, and multimedia networking learning patterns in the chemistry learning process. This research aimed at designing and finding out validity and practicality levels of Science, Technology, Religion, Engineering, Art, and Mathematics approach based interactive media with Nearpod developed on Chemical Bond lesson.  Research and Development (R&D) method was used in this research with Design Development Research (DDR) model, and the steps were analysis, design, development, and evaluation.  This research was conducted at State Senior High School 1 Benai.  The instruments of collecting data were interview sheet, validity test questionnaire, practicality test questionnaire, and student response questionnaire.  The validity test results showed that the percentage results were 94.64% by material experts and 90% by media experts with very valid criteria.  The percentage result of teacher practicality test was 91.66% with very practical criteria, and the percentage result of student response test was 94.88% with very interesting criteria, it can therefore be concluded that interactive media using Nearpod based on the science, technology, religion, engineering, art, and mathematics approach in chemical bonding material is worth trying out as additional teaching material in chemistry lessons.